Risk factors for the development of bronchiolitis obliterans in children with severe adenovirus pneumonia: A retrospective study with dose‐response analysis. Issue 12 (28th February 2020) - Zhong, Linping; Lin, Jilei; Dai, Jihong
Abstract: To investigate and analyze the relevant risk factors for bronchiolitis obliterans (BO) in children with severe adenovirus pneumonia, a retrospective study of children with severe adenovirus pneumonia was performed in 34 cases that developing BO and 105 cases not developing BO in Children's hospital of Chongqing Medical University from January 2015 to February 2019. The multivariate logistic regression analysis was used to identify factors which were significantly associated with development of BO after the univariate analysis, and receiver operating characteristic (ROC) curve analysis was performed to find out the cut‐off value for the significant relevant factors. A nonlinear dose‐response relationship between risk factors and the risk of BO was assessed by restricted cubic spline model. Three factors were independently associated with development of BO, which were length of fever (OR 1.129, 95% CI 1.033‐1.234), dyspnea (OR 3.922, 95% CI 1.060‐14.514) and invasive mechanical ventilation (OR 6.861, 95% CI 1.854‐25.387). The cut‐off value of length of fever were 10.5 days. A linear dose‐response relationship between length of fever and occurrence of BO was observed ( P  = .57 for nonlinearity). Children with severe adenovirus pneumonia who have a longer duration of fever (especially more than 10.5 days), have dyspnea or require invasive mechanical ventilation in the acute phase are more likely to develop BO. Highlights: Different with other researchers have reported, we found 24.5% of severe adenovirus pneumonia developed BO. The independent risk factors for BO proved to be length of fever, dyspnea and invasive mechanical ventilation. Children with severe adenovirus pneumonia who have a longer duration of fever, especially more than 10.5 days, are more likely to develop BO.